Shrouds of glory : from Atlanta to Nashville--the last great campaign of the Civil War - Groom, Winston, 1944-2020. (New York : Atlantic Monthly Press, 1995)
Shrouds of Glory focuses on Confederate General John Bell Hood's decisive actions in the western theater of operations during the final moments of the Civil War. The rich narrative takes us on a journey through the ravaged South to the once vibrant city of Nashville, where General Hood makes a last, futile attempt to preserve the Confederacy.
Weaving eyewitness accounts, journal entries, military communiques, and newspaper headlines with his own straightforward narrative style, Groom constructs a meticulous and atmospheric re-creation of the war - especially the charged battlefields where general and foot soldier alike were thrown into the fray. Groom paints vivid portraits of the major players in the conflict, revealing the character, the faults, the emotions, and, most of all, the doubts that molded the course of the war.
A midsummer's change -- I will go on while I can -- Crazy like a fox -- This army is going to do something wrong -- If you want it, come and take it -- They must be killed -- To conquer the peace -- Go on as you propose -- It is almost worth dying -- The best move come to naught -- Franklin, Tennessee -- Seeing the elephant -- An indescribable fury -- All those dead heroes -- Nashville, Tennessee -- Like a lot of beasts -- Didn't I tell you we could lick 'em? -- A river of fire -- Black care was the outrider.
Includes bibliographical references (p. 293-298) and index.
Keywords: Atlanta Campaign, 1864.; Nashville, Battle of, Nashville, Tenn., 1864.; Georgia -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.